PENGARUH KARAKTERISTIK PEKERJAAN DAN KOMPENSASI TERHADAP KOMITMEN ORGANISASI PADA PT â€œXâ€ JAKARTA - Handaru, Agung Wahyu; Abdillah, Shalahudin; Waspodo, Agung AWS (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purposes of this research are: 1) to describe the job characteristics, the compensation, and the organizational commitment, 2) to analyze the influence of job characteristics towards organizational commitment, 3) to analyze the influence of compensation towards organizational commitment, 4) to analyze the influence of job characteristics and compensation simultaneously toward organizational commitment. Population of the research is the employees of PT â€œXâ€, Jakarta. Samples of the research are 74 permanent employees. Type of the research is descriptive research and the method is explanatory survey. Descriptive analysis results showed: a) 49% total of permanent staff of PT